ANALISIS KESULITAN BELAJAR SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI PENJUMLAHAN PECAHAN DI KELAS V SDN 3 SUKASARI - Hasni Hanifah Firdaus; Winarti Dwi Febriani; Geri Syahril Sidik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Mathematics learning still faces various challenges to this day, one of which is the difficulty students encounter in solving fraction problems, particularly when these problems are presented in the form of word problems. This study aims to describe students' learning difficulties in solving mathematical word problems on the topic of fraction addition in Grade V at SDN 3 Sukasari. The research employs a descriptive qualitative approach with data collection techniques including tests, observations, interviews, and documentation. The subjects consist of six students selected based on high, medium, and low achievement levels. The results indicate that students face various difficulties in solving word problems, which are categorized according to Newman’s theory into five types of errors: reading errors, comprehension errors, transformation errors, process skills errors, and encoding errors. These findings highlight the critical role of teachers in identifying students’ learning obstacles to develop more effective and responsive instructional strategies.